Gr. sonate, 26tes Werk in As ... von L. van Beethoven - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (Germany; Hannover; Adolph Nagel, 2022)
Mid-nineteenth century edition of the Piano Sonata no. 12 in A-flat major, op. 26, published in the series "Sonaten für das Piano Forte allein von L. van Beethoven" by Adolph Nagel in Hannover. With decorative title page for the series listing the piano sonatas opp. 2, 10, 13, 26, 27, and 57, and a piano arrangement of the Sonata for horn and piano, op. 17.